First report of bacterial leaf blight disease of rice caused by Xanthomonas oryzae pv. oryzae in Kenya - Nganga, Everlyne; Brottier, Laurent; Boulard, G.; Blasco, C.; Auguy, Florence; Szurek, Boris; Bigirimana, Joseph (Scientific Societies, 2025)
Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. Oryzae (Xoo) is a devastating disease of rice crops, which can lead to yield losses ranging from 20 to 30% and as high as 50% (Mew 1987). BLB was first reported in Japan in 1884 and is now prevalent in most of the rice-producing countries in Asia. In Africa, Xoo was first reported in Mali and Cameroon (Buddenhagen et al. 1979) and later in many West African countries. Recently, BLB also appears to be spreading in East Africa, with reports from Tanzania (Schepler-Luu et al. 2023) and Madagascar (Raveloson et al. 2023). In June 2023, typical symptoms of BLB such as water-soaked areas and yellowish lesions along the leaf margins and tips were observed on rice plants in the coastal region of Kenya.